Poverty and transitions in health - Maja Adena; Michał Myck (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Using a sample of Europeans aged 50+ from twelve countries in the Survey of Health, Ageing and Retirement in Europe (SHARE) we analyse the role of poor material conditions as a determinant of changes in health over a four-year period. We find that poverty defined with respect to relative incomes has no effect on changes in health. However, broader measures of poor material conditions such as subjective poverty or low relative value of wealth significantly increase the probability of transition to poor health among the healthy and reduce the chance of recovery from poor health over the time interval analysed. In addition to this the subjective measure of poverty has a significant effect on mortality, increasing it by 40.3% among men and by 58.3% among those aged 50-64. Material conditions matter for health among older people. We suggest that if monitoring of poverty in old age and corresponding policy targets are to focus on the relevant measures, they should take into account broader definitions of poverty than those based only on relative incomes.
Keywords: I14; I32; J14; 330